Possibilities of rehabilitation treatment of children with lymphoblastic leukemia (literary review) - Lukashchuk , S.V.; Lemko , O.I. (Medicni Perspektivi, 2021)
According to nowaday protocols of acute lymphoblastic leukemia (ALL) treatment, the percentage of recovering patients has increased significantly. This determines the necessity for comlex long-term rehabilitation, as chemotherapeutic drugs are highly toxic and contribute to the development of comorbid diseases of the gastrointestinal tract, nervous and musculosceletal systems. The purpose of the study was to review and analyze data from foreign and domestic literature concerning possibilities for rehabilitative treatment of children with ALL and to reveal informative methods assessing the effectiveness of rehabilitation. Important elements of rehabilitation goals and assessment of its the effectiveness are the International Classification of Functioning, Disability and Health of Children and Adolescents, and the Quality of Childrens’ Life. Rehabilitation begins at the hospital and includes psychological support for the child with the involvement of psychotherapists and family, as well as the performance of certain physical exercises lasting for 15-30 minutes, which are selected individually, taking into account the functional capabilities and motivation of the child. After the acute period, physical activity is carried out in accordance with an individual plan, which takes into account the peculiarities of the disease and includes active video games, cycling and other activities. Rehabilitation treatment on the basis of sanatorium-resort institutions with the participation of a multidisciplinary team is actual. Such treatment, in addition to physical exercises, includes the use of natural and preformed physical factors in order to influence the manifestations of comorbid pathology, and also contributes to an increase of the social activity and independence of the child. However, the number of such studies is limited, which determines the necessity to develop clear practical recommendations regarding methods of exposure, their duration and intensity.